2009
DOI: 10.1111/j.1600-0404.1993.tb04200.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial doppler in acute ischemic stroke of the middle cerebral artery territories

Abstract: We have investigated the reliability of transcranial doppler compared with cerebral angiography in acute ischemic stroke in the middle cerebral artery territories. We studied 48 patients, 28 men and 21 women, mean age 68.1 (range 54–75), observed within 5 h of the onset of ischemic stroke in the middle cerebral artery territory. Ultrasound evaluation (duplex scanner and transcranial doppler) and cerebral angiography were carried out in close sequence immediately after CT scan. CT was repeated by Day 7 to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 20 publications
2
22
1
1
Order By: Relevance
“…Similar results had been obtained previously by Ley-Pozo 29 and Camerlingo 30 in anterior circulation artery occlusions. In posterior circulation arteries, our results are in agreement with the reports by Brandt 31 and Tsivgoulis 32 who found that TCD had lower sensitivity but high specificity in the diagnosis of occlusive disease.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results had been obtained previously by Ley-Pozo 29 and Camerlingo 30 in anterior circulation artery occlusions. In posterior circulation arteries, our results are in agreement with the reports by Brandt 31 and Tsivgoulis 32 who found that TCD had lower sensitivity but high specificity in the diagnosis of occlusive disease.…”
Section: Discussionsupporting
confidence: 81%
“…16,29,30 The main strengths of our study are that it was conducted in a normal clinical setting in all consecutive patients with acute ischemic strokes who had an acoustic window that allowed TCD examination. There was a very little time difference between CTA and PMD-TCD.…”
Section: Discussionmentioning
confidence: 99%
“…After adjustment for age, neurological deficit on admission, CT scan results, and preexisting risk factors, ultrasound findings remained an independent predictor of outcomes. These results are in line with several small ultrasound studies which emphasize ultrasound as a valid predictor of clinical outcome [7,8,9,10,11]. NAIS also highlights the large number of pathological findings seen within the first hours after stroke which often resolve during the further course of disease.…”
Section: Prognostic Significance Of Early Ultrasound Findingssupporting
confidence: 71%
“…TCD has excellent utility in diagnosis of occlusion within the cerebral vessels with sensitivity and specificity over 90%-particularly in patients where cerebral ischemia is present (Camerlingo et al, 1993). Diagnosis is through absence or a profound reduction of flow at the normal position and depth, and/or consequent lack of signal for the vessels in the immediate vicinity of the occluded region.…”
Section: Intracranial Occlusionmentioning
confidence: 98%